2005
DOI: 10.1007/s10072-005-0378-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double-blind, dose-ranging study to evaluate efficacy and safety of three doses of botulinum toxin type A (Botox) for the treatment of spastic foot

Abstract: Botulinum toxin A (BTX) injections have been used successfully in the treatment of post-stroke foot spasticity, but the optimal dose-response relationship for selected muscles has yet to be established. The aim of this study was to outline beneficial and unwanted effects of three different doses of BTX in the treatment of spastic foot. In this randomised, double-blind, dose-ranging study, 45 spastic feet were randomly allocated to one of three groups, each of which was treated with a different dosage of BTX. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 8 publications
2
100
0
Order By: Relevance
“…8,9 The gait analysis demonstrates that BoNT A injection improves knee flexion during the swing phase: disappearance of the double-bump shape and increase of Ϸ5°in knee flexion amplitude. Stoquart et al 7 found similar results after 200-U BoNT A injection in the RF, and Sung et al 5 found similar results after phenol injection of the RF motor branch.…”
Section: Body Function and Structurementioning
confidence: 98%
See 1 more Smart Citation
“…8,9 The gait analysis demonstrates that BoNT A injection improves knee flexion during the swing phase: disappearance of the double-bump shape and increase of Ϸ5°in knee flexion amplitude. Stoquart et al 7 found similar results after 200-U BoNT A injection in the RF, and Sung et al 5 found similar results after phenol injection of the RF motor branch.…”
Section: Body Function and Structurementioning
confidence: 98%
“…Dose-related BoNT A injection efficacy was clearly demonstrated by a placebo-controlled randomized controlled trial on muscle tone, commonly assessed by the Ashworth scale; 8,9 specifically, the effects of BoNT A injection have been shown only to improve impairments. The impairment reduction may lead to a reduced burden of care, eg, an increase in the passive range of motion facilitating dressing.…”
mentioning
confidence: 99%
“…28,[38][39][40][41] It has been suggested that proper choice of muscles and individualized doses of BoNT type A can improve function in selected poststroke patients. 42 Advantages of BoNT over oral medications is target specificity (ie, exerting significant changes only in injected muscles) and better adverse event profile.…”
Section: Botulinum Neurotoxinsmentioning
confidence: 99%
“…These toxin products have an upper dosage limit, and their adverse events have become serious issues, speculated as after-effects of diffusion after high-dose administration [12][13][14][15]. Therefore, a preparation with greater therapeutic efficacy at lower dosages, and showing less diffusion in the body than existing drugs, has been sought.…”
mentioning
confidence: 99%